Improved algorithms for determination of particle directions with Timepix3. (1st January 2022) - Mánek, P.; Bergmann, B.; Burian, P.; Garvey, D.; Meduna, L.; Pospíšil, S.; Smolyanskiy, P.; White, E.
Abstract: Timepix3 pixel detectors have demonstrated great potential for tracking applications. With 256 × 256 pixels, 55 µm pitch and improved resolution in time (1.56 ns) and energy (2 keV at 60 keV), they have become powerful instruments for characterization of unknown radiation fields. A crucial pre-processing step for such analysis is the determination of particle trajectories in 3D space from individual tracks. This study presents a comprehensive comparison of regression methods that tackle this task under the assumption of track linearity. The proposed methods were first evaluated on a simulation and assessed by their accuracy and computational time. Selected methods were then validated with a real-world dataset, which was measured in a well-known radiation field. Finally, the presented methods were applied to experimental data from the Large Hadron Collider. The best-performing methods achieved a mean absolute error of 1.99° and 3.90° in incidence angle θ and azimuth φ, respectively. The fastest presented method required a mean computational time of 0.02 ps per track. For all experimental applications, we present angular maps and stopping power spectra.